On the influence of second use, future battery technologies, and battery lifetime on the maximum recycled content of future electric vehicle batteries in Europe. (15th April 2021) - Abdelbaky, Mohammad; Peeters, Jef R.; Dewulf, Wim
Highlights: A novel forecasting model is developed to include second-use of vehicle batteries. Waste recycling potential is estimated with scenarios and Monte Carlo simulations. Cobalt content of recycled EV batteries may fulfil 91% of Europe's 2040 EV demand. Global sensitivity analysis is used to decompose the model's output variance. Abstract: The European Union is promoting the uptake of low emission vehicles to reduce greenhouse gas emissions from transportation. However, this transition will increase the demand for five important battery raw materials; i.e. lithium, nickel, cobalt, copper, and graphite. Therefore, a substance flow analysis and forecasting model are proposed to investigate the flow of these materials through the different lifecycle stages of electric vehicle batteries. The model forecasts that by 2040, the vehicle stock will be from 72 to 78 million vehicles, while the second use stock will be from 3 to 11 million batteries. In addition, the annual recycling waste stream in 2040 will grow to roughly 3 million batteries with a capacity of 125 GWh. Results indicate that this waste stream could cover between 10% and 300% of future raw materials demand for electric vehicles. The width of this range is dominated by uncertainties on the rapidly evolving material composition of automotive batteries and the possible commercialization of cobalt-free battery technologies. The remaining uncertainty is attributed to the battery lifetime in vehicle use and potential second use of retired batteries.